HUMAN VALUES IN TERE LIYE’S NOVEL BIDADARI-BIDADARI SURGA - Hidayati Hidayati; Arifuddin Arifuddin; Ratna Sari Dewi (Universitas Islam Sumatera Utara, 2021)
The research is based on the reality depicted in the novel Bidadari-Bidadari Surga by Tere Liye that the human values of the millennial generation are currently starting to fade. Human value is a basic trait that humans have to love each other and not be concerned with self-interest. This study aims to provide input to the community, especially millennial generations, that human values must be maintained to obtain a harmonious life. Humanitarian problems arise when a sense of concern and tolerance for others suffers a setback due to the non-functioning of the institution optimally. The method used is descriptive qualitative showing the phenomena of human values in society by collecting written data in the forms of words, phrases and sentences containing human values in the novel. The data collection is done by means of note-taking method, referring to the topics of discussion. The results show that human values in the forms of love, sacrifice and tolerance are depicted in the novel Bidadari-Bidadari Surga by Tere Liye. The results of this study are expected to raise awareness among the millennial of the importance of human values for the continuity of peaceful and harmonious life to improve lifestyle quality on an ongoing basis.